The radiation shielding offered by the commercial glass installed in Bangladeshi dwellings - Yasmin, Sabina; Zahariman, Siti Rozaila; Khandaker, Mayeen Uddin; Barua, Bijoy Sonker; Chowdhury, Faruque-Uz-Zaman; Rashid, Md. Abdur; Bradley, David Andrew (Taylor & Francis, 2018)
One sign of a vibrant Bangladeshi economy has been the move away from the use of more traditional housing materials towards a preference for modern constructional media. Glass, one such example, used both decoratively and in a structural context, offers various advantageous properties and facets including a protective feature against radiation that has not previously been considered. Current interest examines the dosimetric possibilities offered by the commercial glass as a secondary shield and also in retrospective ionising radiation exposure analysis. Four popular brands of window glass are investigated, all available within the local market (PHP-Bangladesh, Usmania-Bangladesh, Nasir-Bangladesh and Rider-China), all with the same thickness and colour, varying in terms of elemental weight fractions as evaluated by energy dispersive X-ray analysis. As potential attenuators of transmitted radiation thereby forming secondary barriers against radiation exposure from penetrating radiations, the four brands of glass have been studied using photon energies from 59 up to 1332 keV, a range of values representative of that potentially encountered in incidents. Use has been made of a well-shielded high-purity germanium γ-ray spectrometer and associated electronics, providing for evaluation of the characteristic barrier parameters of half-value layer, radiation protection efficiency and effective atomic number (Zeff). Of the four brands investigated, Rider provides superior secondary shielding performance. Concerning potential retrospective dosimetry the effective atomic number of the glass samples are comparable with that of the commercial thermoluminescence (TL) dosimeter TLD-200. At high doses, the TL yields are sufficient to provide for retrospective accident dosimetry.